PERCEIVED QUALITY OF HEALTH CARE BY HEALTH CARE SYSTEM LEVEL AMONG TYPE 2 DIABETIC PATIENTS IN NORTHERN THAILAND - Wangwonsin, Artittaya; Jariya, Wutthichai; Phetphum, Chakkraphan (Southeast Asian journal of tropical medicine and public health, 2020)
Quality of healthcare may affect disease outcomes. In this study, we aimed to determine the perceived quality of healthcare by healthcare system level among type 2 diabetes patients (T2DM) in order to inform healthcare interventions to improve outcomes in these patients. The system levels evaluated were health centers without a physician (n=5), health centers with a physician (n=5), district hospitals (n=5) and provincial hospitals (n=3). Study subjects were purposely selected from T2DM attending the study institutions. Each subject was asked to complete the Thai Patient Assessment of Chronic Illness Care (Thai PACIC) questionnaire. A total of 1408 subjects were included in the study (health centers without a physician: n=522; health centers with a physician: n=183; district hospitals: n=413; provincial hospitals: n=290). Seventy-three point five percent of subjects were female; the mean age of study subject was 57.4 years. The Thai PACIC was scored from 0 to 100; the higher the score the better the perceived quality of care. The mean Thai PACIC scores for health centers without a physician, health centers with a physician, district hospitals and provincial hospitals were 80.0, 79.6, 81.6 and 72.0, respectively. All levels of healthcare institutions were perceived by subjects to provide "adequate" health care but these can be improved. The mean overall Thai PACIC score for the provincial hospitals was significantly (p < 0.05) lower than the other levels. Further studies are needed to determine why the perceived quality of care at provincial hospitals was lower than the other levels and if this associated with poorer outcomes.